Holy Spirit and Ghost：A Brief Introduction to Christianity and Communism - LI, Ling (Journal of Research for Christianity in China (JRCC), 2025)
This article discusses the relationship between Christianity and communism. Firstly, this article begins with a review of the origins of communism. Then, the article will review the characteristics of early Christianity's "communism" and conclude with a definition of Christian communism. The author argues that Christian communism is an ideal social form gradually formed from the early church's economic practice of "communal sharing" in the face of the widening gap between the rich and the poor and the increasing conflicts between social classes due to social injustice. This paper is useful for considering the relationship between Christianity and communism.